A Contextual Look at Safe Routes to School Implementation in Texas. (January 2016) - Atteberry, Heather; Dowdy, Diane; Oluyomi, Abiodun; Nichols, Donna; Ory, Marcia G.; Hoelscher, Deanna M.
In an effort to understand factors influencing the implementation and outcomes of the Safe Routes to School (SRTS) program in Texas, interviews were conducted in 2014 with 34 community- and state-level stakeholders involved in the 2007 SRTS grant program. Participants were asked a series of multiple-choice and open-ended questions about SRTS program planning, implementation, and sustainability. Transcribed responses were organized and grouped according to thematic elements using standard qualitative methods. Results indicate the SRTS program was perceived as beneficial by providing funds for both infrastructure and education projects. Although most community representatives reported accomplishments toward planned goals (improved infrastructure and perceived increase in active commuting), many had significant challenges including lack of communication and up-front funding, and difficulty navigating the regulatory process. Future SRTS programs should be structured to be more compatible with community-based needs and limitations, provide adequate underlying infrastructure and resources, and include at least partial funding up-front.